The importance of intonation for children’s understanding of verbal irony - Smith, Jordanna; Glenwright, Melanie (Frontiers in Psychology, 2025)
Verbal irony refers to any utterance in which the speaker’s words mean something different from their intended meaning (e.g., “You’re really on top of things” said to a disorganized person). For children who are just learning to recognize verbal irony, a crucial cue to the ironist’s intended meaning is their intonation. In this narrative review, we describe research methods for examining how intonation influences children’s understanding of verbal irony and the task demands researchers need to consider when designing these studies. Next, we examine how children weigh different cues to verbal irony as they grow older, and we identify cross-linguistic factors that can impact children’s use of intonation for irony comprehension. We offer suggestions for planning future studies on this topic by stressing the importance of reducing task demands, acoustically analyzing directional frequency changes, examining children’s intonation consideration in languages other than English, and comparing across tonal and non-tonal languages.